SOCIEDAD CIVIL Y EDUCACIÓN: REFLEXIONES DESDE UNA PERSPECTIVA DE PAZ - Poveda Villafañe, Liduvina (2014)
Este artículo aborda los significados de la paz y el rol de la sociedad civil en el propósito deavanzar hacia este derecho. Se considera que es relevante la mediación pedagógica del docenteen la construcción de la paz desde el aula. Se procede al análisis del hacer y los saberes de lasociedad civil en procesos que implican pensar un posconflicto. Las reflexiones no culminanen un aporte concluyente sino que se ciñen a observaciones e inmersión en el contexto-paísy en las lecturas coyunturales que la autora realiza asiduamente sobre la paz; la cual desde laeducación es un camino para el fortalecimiento de las apuestas institucionales de integraciónpara países de América Latina.AbstractThis article discusses the meanings of peace and the role of civil society in order to move towards theright. It is considered as an important pedagogical mediation of teachers in peace building from theclassroom, considering that their actions impact on attitudes and students. It also discusses the makingand knowledge of civil society in the processes involved in post-conflict thinking. These reflections donot culminate in an aside conclusive but are restricted to observations and immersion in the context / country and joint readings that the author has done in the field of study of peace from the Colombianconflict, although very little text refers to it, if it allows cross some own visions that are shared withresearchers / research that advance peace studies.Keywords peace; peace education; civil society and post-conflict.